Impact Analysis of Metallization Design and Recombination Losses on Performance of Crystalline Silicon Solar Cells - Amin N.; Santhiran S.; Kassim N.M.; Alkahtani A.A.; Islam M.A.; Mohd Yusof M.Y. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Using Griddler software, this study aims to select the optimal metallization design by analyzing the impact of the number and sizes of busbars and fingers on a solar cells performance. There is interest in the PV industry to reduce the finger size toward 25 ?m in upcoming years. It is shown that an increase in the number and size of busbars and fingers causes an increase in the fill factor